Second International Conference on Innovative Computing, Informatio and Control (ICICIC 2007) 2007
DOI: 10.1109/icicic.2007.309
|View full text |Cite
|
Sign up to set email alerts
|

Feature Selection and Classification Techniques for Multivariate Time Series

Abstract: Multivariate time series (MTS) data sets are common in many multimedia, medical, process industry and financial applications such as gesture recognition, video sequence matching, EEG/ECG data analysis or prediction of abnormal situation or trend of stock price. MTS data sets are high dimensional as they consist of a series of observations of many variables (multidimendsional variable) at a time. For analysis of MTS data in order to extract knowledge, a compact representation is needed. For feature subset selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…We chose to annotate the data at 10Hz, a higher rate than our previous study, because we wanted to capture communication cues that cannot be detected with a smaller data frequency, such as glancing at a person to see what they are doing. We used a machine learning technique called feature selection (Chakraborty, 2007;Guyon & Elisseeff, 2003) to automatically extract sequences of events that are predictive of the physical reaching actions. Then, we used these sequence features in a variety of machine learning classifiers (Mitchell, 1997) and found that a decision tree classifier (Fig.2) performs best on the evaluation data set.…”
Section: Learning the Communication Of Intentmentioning
confidence: 99%
“…We chose to annotate the data at 10Hz, a higher rate than our previous study, because we wanted to capture communication cues that cannot be detected with a smaller data frequency, such as glancing at a person to see what they are doing. We used a machine learning technique called feature selection (Chakraborty, 2007;Guyon & Elisseeff, 2003) to automatically extract sequences of events that are predictive of the physical reaching actions. Then, we used these sequence features in a variety of machine learning classifiers (Mitchell, 1997) and found that a decision tree classifier (Fig.2) performs best on the evaluation data set.…”
Section: Learning the Communication Of Intentmentioning
confidence: 99%
“…In [18] it is successfully demonstrated that the classification of feature-based MTS is faster than other methods. In [19] this is confirmed, where preprocessing was used to select relevant features and remove redundant features before classification. However, MTSC is a complex problem, because the predictors can have many features, there can be many relationships between features, and they depend on the time variable.…”
Section: Introductionmentioning
confidence: 88%
“…The choice of appropriate features plays an important role in this approach. A number of techniques has been proposed for feature subset selection by using compact representation of high dimensional time series into one row to facilitate the application of traditional feature selection algorithms like recursive feature elimination (RFE), zero norm optimization and so forth [10,11]. Time series shapelets, characteristic subsequences of the original series, are recently proposed as the features for time series classification [12].…”
Section: Introductionmentioning
confidence: 99%